The success and complications of complete-arch implant-supported fixed monolithic zirconia restorations: a systematic review - Vozzo, Ludovico Maria (2023)
In full-arch rehabilitation with implant-supported fixed prostheses, using monolithic zirconia seems to have several advantages regarding function and esthetics. However, the current scientific evidence is still limited. Thus, the aim of this investigation was to systematically review the literature on monolithic zirconia restorations for full-arch rehabilitation, particularly pursuing the survival rate and mechanical and biological complications. This study’s protocol was registered in PROSPERO (CRD42022301799). The primary literature search was performed in PubMed/MedLine and Web of Science, and a manual search was performed (checking cross-references). The focused question was, “In an adult population with one or both edentulous arches (P), the oral rehabilitation with implant-supported fixed-monolithic zirconia (full arch) (I), compared with oral rehabilitation using fixed-metal-ceramic prosthesis on implants (C), did show superior clinical results (O) in a minimum follow-up of 1 year (T)?” Inclusion and exclusion criteria were defined. Joana Briggs Institute tools were used to evaluate the quality of the studies. Meta-analysis was performed for the variable survival rate (%), applying the specific continuous moderator (follow-up). Data heterogeneity (I2) was assessed. From the initial search, 327 references were obtained. After eliminating duplicates and applying the inclusion/exclusion criteria by reading the titles, abstracts, and full text, seven articles were included. All included articles were observational longitudinal retrospective studies, with a number of prostheses between 7 and 2039. The mean age was 60 years, and the mean follow-up was 49.7 months. They had mandibular, maxillary, or bimaxillary rehabilitations, always with screw-retained retention, with an average survival rate of 97.23%. The number of implants ranged between four and eight. The quality of the articles was over 70%, and the heterogeneity was considered low (I2 = 28.64%). Within a mean follow-up of around four years, full-arch implant-supported monolithic zirconia rehabilitations had a high survival rate and minimal complications.